Pathogenetically justified tactics of management of pregnancy with retrochorial hematoma - K. G. Sultangadzhieva; N. N. Babaeva; E. S. Egorova; J. Kh. Khizroeva; M. G. Sultangadzhiev (Акушерство, гинекология и репродукция)
Introduction. Retrochorial hematoma (RH) often detected during routine ultrasound examination represents one of the multiple causes resulting in early pregnancy loss. RH results from the detachment of the chorionic plate from the vertebrae of the uterine decidual membrane and may lead to complicated course of pregnancy.Aim: to develop a differential approach to diagnose and manage pregnancy with RH.Materials and Methods. A prospective open-ended interventional non-randomized study was conducted by enrolling 170 women. The main group consisted of 85 pregnant women with RH, which were divided into 2 groups: group I (n = 45) – patients with RH and burdened obstetric history; and group II (n = 40) – pregnant women with RH without a history of obstetric complications. The control group included 85 women with uncomplicated pregnancy. The incidence of hereditary thrombophilia was assessed by measuring rate of high thrombogenic risk mutations in the genes of factor (F) V Leiden and prothrombin (FII) G20210A; blood levels of lupus anticoagulant (LA) and anti-cardiolipin antibodies (aCL), β2-glycoprotein 1 (β2-GP1), annexin V and prothrombin; ADAMTS-13; rate of low thrombogenic risk polymorphisms, prevalence and spectrum of bacterial-viral infections.Results. It was revealed that women with RH had occasional genetic and acquired hemostasis defects as well as impaired florocenosis of the urogenital tract. Defects in the fibrinolysis system prevailed among the hereditary hemostasis defects: 75.5 % in group I, 32.2 % in group II, and 4.7 % in the control group. No decrease in the activity of natural anticoagulants – antithrombin and protein C was found. Among the acquired thrombophilic conditions, a large proportion of circulating antiphospholipid antibodies (APA) was found: 46.6 % in group I, 27.5 % in group II, and 2.3 % in the control group. Cervicitis of nonspecific etiology prevailed among dysbiosis signs: 53.3 % in group I, 47.5 % in group II and 11.7 % in the control group.Conclusion. RG formation is a multifactorial process, which pathogenesis involves both genetic and acquired factors such as APA, especially in combination with genetic thrombophilia (FV Leiden and FII G20210A), as well as inflammatory or pro-inflammatory status. We consider that all patients with RG as well as those with former RG are indicated to undergo the above-mentioned studies. It is advisable to include tranexamic acid, progesterone, low molecular weight heparins and antibiotics in the therapy regimen if indicated.